2018
DOI: 10.1103/physrevfluids.3.094601
|View full text |Cite
|
Sign up to set email alerts
|

Intermittency enhancement in quantum turbulence in superfluidHe4

Abstract: Intermittency is a hallmark of turbulence, which exists not only in turbulent flows of classical viscous fluids but also in flows of quantum fluids such as superfluid 4 He. Despite the established similarity between turbulence in classical fluids and quasi-classical turbulence in superfluid 4 He, it has been predicted that intermittency in superfluid 4 He is temperature dependent and enhanced for certain temperatures, which strikingly contrasts the nearly flow-independent intermittency in classical turbulence.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 56 publications
(99 reference statements)
3
16
0
Order By: Relevance
“…Upon approaching smaller and smaller scales, however, the matching cannot be complete, dissipation due to mutual friction starts to operate (the roll-off exponent becomes gradually steeper), and one component starts to act as a source or drain for the other. This results in an increase of intermittency corrections, as predicted by Boue et al ( 44 ) and experimentally confirmed by Varga et al ( 45 ).…”
Section: Quantum Turbulence In the Two-fluid Regimesupporting
confidence: 80%
See 1 more Smart Citation
“…Upon approaching smaller and smaller scales, however, the matching cannot be complete, dissipation due to mutual friction starts to operate (the roll-off exponent becomes gradually steeper), and one component starts to act as a source or drain for the other. This results in an increase of intermittency corrections, as predicted by Boue et al ( 44 ) and experimentally confirmed by Varga et al ( 45 ).…”
Section: Quantum Turbulence In the Two-fluid Regimesupporting
confidence: 80%
“…Geometrically it means that the turbulence contains, within a tangle of random vortex lines, partially polarized vortex lines, or bundles, with relatively large coarse-grained superfluid vorticity. We also note that the inertial range in the turbulent normal fluid was observed by Guo and coworkers ( 45 ) by visualizing grid-generated turbulence using neutral He molecules, allowing one to measure transverse velocity structure functions selectively in the normal fluid. This is possible due to the small size of He triplet molecules that are effectively part of the normal fluid and do not trap vortex lines above 1 K ( 49 ).…”
Section: Quantum Turbulence In the Two-fluid Regimementioning
confidence: 54%
“…Most experimental, theoretical and numerical studies have addressed quantum turbulence in its simplest form: statistically-steady, homogeneous and isotropic. These studies have revealed similarities and differences with respect to ordinary turbulence, in terms of energy spectra [2][3][4], decay [5,6], intermittency [7][8][9] and velocity statistics [10][11][12]. Much less is known about turbulence which is inhomogeneous, in particular turbulence which is initially confined in a small region of space and is free to spread out.…”
Section: Introductionmentioning
confidence: 99%
“…This fs-laser beam can create a thin line of He * 2 molecular tracers with a 13-s radiative decay lifetime [26]. Due to their small size (about 6 Å in radius [27]), these molecules are entrained by the viscous normal fluid above 1 K without being affected by the superfluid vortices [28], thereby allowing quantitative normal-fluid velocityfield measurements [29][30][31][32][33][34][35][36]. We then utilize a laserinduced fluorescence technique to image the tracer line [37].…”
Section: Methodsmentioning
confidence: 99%